A nationwide assessment of wastewater use in Pakistan: an obscure activity or a vitally important one? - Ensink, Jeroen H.J.; Mahmood, Tariq; Hoek, Wim van der; Raschid-Sally, Liqa; Amerasinghe, Felix P. (2004)
A nationwide assessment in Pakistan showed that the direct use of untreated wastewater for agriculture, particularly vegetable production, was common in most cities. The main reasons for this use were the absence of alternative water sources, the reliability of the wastewater supply, the nutrient value and the proximity to urban markets. It was estimated that 26% of the total domestic vegetable production of Pakistan was cultivated with wastewater. The importance of the wastewater was reflected in high water and land fees. Policy makers have to take the importance for local livelihoods and food security into account when making decisions regarding direct wastewater use